Contingenza e retribuzione protetta: una risposta - A. CASSONE; C. MARCHESE; F. SCACCIATI (Moneta e Credito, 2014)
In this brief note the authors respond to L. Spaventa’s criticism of the methodology used to determine the level of protected pay, in their book Inflazione e Salari. In a recent article L. S. has raised some criticisms of the methodology by which we solve the problem of identifying the protected level of pay, is instantaneous, both in cumulative terms, in the book Inflation and Wages. The fundamental criticism concerns the taking over of 100 the value of the price index at time t = 0, from which derives, according to Intimidate, an underestimation of the salary protected. Obviously, any estimate of remuneration protected can not refer to some initial value of the price index, on the other hand how many times the same Scare highlights. The authors explain why the choice made by them is justified.